2021
DOI: 10.1155/2021/1434546
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Profiling of Spermatozoa Reveals Correlations between Morphology and Gene Expression: A Novel Biomarker Panel for Male Infertility

Abstract: Choosing spermatozoa with an optimum fertilizing potential is one of the major challenges in assisted reproductive technologies (ART). This selection is mainly based on semen parameters, but the addition of molecular approaches could allow a more functional evaluation. To this aim, we used sixteen fresh sperm samples from patients undergoing ART for male infertility and classified them in the high- and poor-quality groups, on the basis of their morphology at high magnification. Then, using a DNA sequencing met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…In depth omics studies have recently been carried out in human and animal spermatozoa to provide a better understanding of male fertility at the genes [2][3][4][5], transcript [6][7][8], protein [9][10][11][12][13][14], and metabolite levels [6,11,[15][16][17][18]. Although these huge fertility-related omics datasets can offer prospective sources for discovering male fertility biomarkers which contribute to assess male fertility potential or sperm dysfunctions, these studies invariably contain information that is unrelated to male fertility status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In depth omics studies have recently been carried out in human and animal spermatozoa to provide a better understanding of male fertility at the genes [2][3][4][5], transcript [6][7][8], protein [9][10][11][12][13][14], and metabolite levels [6,11,[15][16][17][18]. Although these huge fertility-related omics datasets can offer prospective sources for discovering male fertility biomarkers which contribute to assess male fertility potential or sperm dysfunctions, these studies invariably contain information that is unrelated to male fertility status.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive and comparative omics studies have recently been conducted in animals and humans to provide a better understanding of the complex multifactorial processes linked to male fertility at the gene [ 2 5 ], transcript [ 6 8 ], protein [ 9 14 ], and metabolite levels [ 6 , 15 18 ]. The development of new molecular methodologies to determine male fertility potential or sperm dysfunction has been facilitated by the accumulation of massive fertility-related omics datasets that serve as promising resources for identifying biomarkers of male fertility [ 10 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal sperm morphology can impact their ability to successfully fertilize an egg, influencing both natural conception and the results of procedures such as IVF and ICSI. A study conducted by Cassuto et al, 2022 involved a total of 16 couples enrolled for IVF protocol and revealed a significant correlation between morphology and gene expression in spermatozoa, a new tool to explore male infertility [51]. The antioxidant treatment can have an ameliorative effect on the sperm morphology.…”
Section: Discussionmentioning
confidence: 99%
“…TRPM3 is involved in the regulation of inflammation through the release of neuropeptides ( 33 ). Intriguingly, a study profiled the global DNA methylation in sperm and found the aberrant modification of TRPM3 in patients with low morphology scores ( 34 ). Meanwhile, miR-22-5p, the impresser of TRPM3, was found to be upregulated in testicular tissue from patients with the non-obstructive azoospermia ( 35 ).…”
Section: Discussionmentioning
confidence: 99%